MicroRNA-29a induces apoptosis via increasing the Bax:Bcl-2 ratio in dermal fibroblasts of patients with systemic sclerosis. (September 2015) - Jafarinejad-Farsangi, Saeideh; Farazmand, Ali; Mahmoudi, Mahdi; Gharibdoost, Farhad; Karimizadeh, Elham; Noorbakhsh, Farshid; Faridani, Habibeh; Jamshidi, Ahmad Reza
Abstract The most prominent feature of systemic sclerosis (SSc) and other diseases associated with fibrosis is the prolonged activation of fibroblasts not eliminated by apoptosis, hence characterized by accumulation of more extra cellular matrix (ECM). We tend to verify if microRNA-29a (miR-29a) as an anti-fibrotic factor could induce apoptosis in SSc fibroblasts. We did not detect apoptosis in SSc fibroblasts. We found that Bcl-2 expression was upregulated in SSc fibroblasts and the ratio of Bax:Bcl-2 in these cells was significantly lower (p = 0.02) compared to normal fibroblasts. Transfection of both SSc and transforming growth factor-β (TGF-β) stimulated fibroblasts by miR-29a mimic, significantly decreased the expression of two anti-apoptotic members of the Bcl-2 family, Bcl-2 (p = 0.0005, p = 0.01) and Bcl-XL (p = 0.0001, p = 0.006), resulted in enhanced Bax:Bcl-2 ratio and induced a high rate of apoptosis. Recently, miR-29 has been introduced as an anti-fibrotic factor with potential therapeutic effect on SSc. Until now, it has not been proposed whether there is a relationship between miR-29a and apoptosis in SSc. According to our results, it seems that miR-29a is a potent inducer of apoptosis in SSc fibroblasts and an attenuator of ECM production in these cells. MiR-29a disrupted the expression profiling of Bcl-2 family proteins (Bax, Bcl-2 and Bcl-XL) which is the central point of dynamic life-death rheostat in many apoptotic pathways. Furthermore, dermal fibroblasts from patients with SSc showed elevation in TNF-α mRNA levels, while restoration of miR-29a decreases TNF-α production in these cells. Although further molecular studies are necessary to investigate the underlying apoptotic pathways, the present findings suggest that anti-fibrotic and pro-apoptotic properties of miR-29a could provide novel benefits toward the development of fibroblast-specific anti-fibrotic therapies.